Blood biochemistry changes in a minipig infarction model - Kőrösi, Dénes; Göcző, Ágoston; Varga, Noémi; Garamvölgyi, Rita; Balogh, Nándor; Farkas, Kornélia; Vorobcsuk, András (Frontiers in Veterinary Science, 2025)
IntroductionThe present study aimed to assess changes in biochemical parameters during the adaptation of the myocardial infarction model to a conventional Hungarian minipig breed. According to our hypothesis, changes in the blood level of the necroenzymes are not only related to the interventional procedure but are also influenced by peri-procedural animal keeping and treatment conditions.MethodsClosed chest acute myocardial infarction (AMI) was induced by balloon occlusion for 90 min in the left anterior descendent coronary artery (LAD) in 24 adult, female Pannon minipigs followed by reperfusion. Blood samples were taken before AMI, and immediately after the reperfusion, during the cardiac magnetic resonance imaging (cMRI) on days 3 and 30. Aspartate transaminase (AST), alanine aminotransferase (ALT), creatine kinase (CK), lactate dehydrogenase (LDH), and high-sensitivity troponin I were determined.ResultsWhile the parameters measured at baseline remained within physiological ranges, a notable elevation was seen in comparison with the results observed on day 30. This phenomenon was evident in all the laboratory parameters tested, except hs-troponin. The results for AST, ALT, LDH, and CK were statistically significant (p = 0.011, p = 0.001, p = 0.013, and p = 0.001, respectively). A statistically significant difference was observed between the baseline and 30-day AST/ALT ratio (p = 0.00514).DiscussionThe elevated levels of necroenzymes observed at baseline are likely to be a consequence of the physical and social stress imposed by the study design on the minipigs during the 72-h period prior to intervention. It is essential to define the optimal timing of baseline blood tests to ensure the reliability of the biochemical profile in a large animal infarction model.